2018
DOI: 10.1007/s00167-018-5036-x
|View full text |Cite
|
Sign up to set email alerts
|

Transportal central femoral tunnel placement has a significantly higher revision rate than transtibial AM femoral tunnel placement in hamstring ACL reconstruction

Abstract: Level II-prospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 29 publications
1
35
0
Order By: Relevance
“…35,53 Additionally, higher failure rates have been reported in a number of studies in which an anatomic surgical technique was performed, suggesting that a more anatomic ACL graft placement may lead to greater forces being placed on the ACL graft, resulting in a subsequent increase in risk of graft rupture. 9,42…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…35,53 Additionally, higher failure rates have been reported in a number of studies in which an anatomic surgical technique was performed, suggesting that a more anatomic ACL graft placement may lead to greater forces being placed on the ACL graft, resulting in a subsequent increase in risk of graft rupture. 9,42…”
mentioning
confidence: 99%
“…35,53 Additionally, higher failure rates have been reported in a number of studies in which an anatomic surgical technique was performed, suggesting that a more anatomic ACL graft placement may lead to greater forces being placed on the ACL graft, resulting in a subsequent increase in risk of graft rupture. 9,42 More recently, a significant focus has been placed upon the anterolateral complex (ALC), a combination of structures on the lateral side of the knee that have been demonstrated to aid in the control of anterolateral rotatory laxity. 8,15,20,39 The ALC includes the superficial and deep iliotibial band (ITB), the capsulo-osseous layer of the ITB, 19,27 and a thickening of the lateral capsule referred to as the anterolateral ligament (ALL).…”
mentioning
confidence: 99%
“…Thus, the findings of recent clinical studies, suggesting a significantly higher rate of graft failure in the central footprint ACL reconstruction group than in the AM footprint reconstruction group, could be reinforced by our results. 6,39 However, the results and clinical relevance of this study should be carefully interpreted in light of its several limitations. First, the effect on potential graft failure of an approximate 10 difference in GTA and 4-MPa difference in contact stress has yet to be clearly defined.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, an excessively inferior femoral tunnel was created, resulting in a graft location within the indirect insertion area where the contribution of the load was relatively low. 29,36,42 Furthermore, several studies, such as the Danish Knee Ligament Reconstruction Register 39 and the prospective and comparative study of Clatworthy et al, 6 reported that the central graft yielded a higher revision rate than the AM graft. The Danish registry study proposed that the steep technical learning curve resulted in higher failure using the transportal technique targeting the femoral central footprint.…”
Section: Discussionmentioning
confidence: 99%
“…“In addition to graft choice, the surgeon must also decide which surgical technique to use. Anteromedial and transtibial techniques are the most commonly used, with most orthopaedic surgeons using the anteromediel technique, as it allows for unconstrained anatomic placement of both the tibial and femoral tunnels” 33…”
Section: Contralateral Acl Rupturementioning
confidence: 99%